2020
DOI: 10.1093/neuopn/okaa008
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Spectrum of Major Neurovascular Events Among COVID-19 Patients: A 3-Center Experience

Abstract: BACKGROUND Preliminary data suggest that Coronavirus Disease-2019 (COVID-19) is associated with hypercoagulability and neurovascular events, but data on outcomes is limited. OBJECTIVE To report the clinical course and outcomes of a case series of COVID-19 patients with a variety of cerebrovascular events. METHODS We performed a multicentric, retrospective cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 15 publications
0
22
0
11
Order By: Relevance
“…A multicenter study of 26 patients with COVID-19 and ischemic or hemorrhagic events reported that 27% were younger than 50 years 20 . In addition, the report indicated that two of the 15 patients with great vessel stroke were younger than 50 years and no prior stroke risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multicenter study of 26 patients with COVID-19 and ischemic or hemorrhagic events reported that 27% were younger than 50 years 20 . In addition, the report indicated that two of the 15 patients with great vessel stroke were younger than 50 years and no prior stroke risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Un estudio multicéntrico de 26 pacientes con COVID-19 y eventos isquémicos o hemorrágicos informó que el 27% eran menores de 50 años 20 . Además, el informe indicó que dos de los 15 pacientes con accidente cerebrovascular de gran vaso eran menores de 50 años y no tenían factores de riesgo de accidente cerebrovascular previos.…”
Section: Discussionunclassified
“… 12 A multicentre series of 26 patients with COVID-19 and either ischaemic or haemorrhagic events reported that 27% were younger than 50 years. 16 Additionally, the report stated that two of 15 patients with large vessel stroke were younger than 50 years and without previous stroke risk factors. In this study, consistent with other case series, patients with COVID-19 fare worse in terms of clinical outcomes than patients with stroke who do not have COVID-19.…”
mentioning
confidence: 99%
“…This partly reflects the demographics of Qatar; nearly 90% of the population are foreign workers and the median age of the population is 32 years [ 7 ]. Nevertheless, other countries are recognizing that younger patients with COVID-19 can suffer strokes [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%